Mantle contributions to global tungsten recycling and mineralization - Jie-Hua Yang; Jing-Hua Wu; Mei-Fu Zhou; Rui-Zhong Hu; Jun-Hong Zhao; Anthony E. Williams-Jones; Qian Hu; Run-Sheng Yin (Communications Earth & Environment)
Abstract Tungsten deposits are typically associated with crust-derived evolved granitoids. Whether the mantle has contributed to tungsten mineralization, however, is unknown. Here, we provide new and compiled helium‒argon‒mercury‒strontium‒neodymium isotope data in South China and tungsten provinces elsewhere to evaluate this contribution. Our analysis shows that oceanic-subduction-related extension is more likely to facilitate intense tungsten mineralization than other geodynamic processes, e.g., continental collision, post-collisional extension, and intracontinental rifting. During this process, the mantle provides heat for inducing slab devolatilization, whereby abundant helium‒argon‒mercury‒(fluorine) are mobilized into the crust. The 1.8‒1.2 Ga neodymium model ages of the source rocks coincide with the Nuna supercontinent cycle, together with deep-time zircon data, suggesting that the considerable tungsten enrichment of the crust over geological time resulted from mantle-plume-related activities. The above hypothesis is confirmed by the proportion of tungsten-rich basement rocks in major tungsten provinces, highlighting the essential role of the mantle in tungsten recycling and mineralization.